TEACHING VOCABULARY BY USING HYPONYMY - Ihsan, Muhammad; Supardi, Iwan; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract : The purpose of this research was to find out the effectiveness of the use of Hyponymy in Teaching Vocabulary. This research was done using a pre-experimental method with intact-group comparison design. In this research, the population of the research was divided into two groups; experimental group and control group. The tool of data collecting was written test. The students were asked to answer 30 questions of multiple choise. From the data analysis, it was found that Hyponymy significantly improved students’ vocabulary achievement. It can be seen from the difference of the mean score of experimental group (76.96) and control group (48.62). Furthermore, the effect of the use of Hyponymy was strong in teaching vocabulary since the effect size is 1.83 (> 1.00) or categorized as strong effect. In conclusion, the use of Hyponymy is effective in teaching vocabulary to the eighth grade students of MTs Aswaja Pontianak in academic year 2014/2015. Keywords : Teaching Vocabulary, Hyponymy Abstrak : Penelitian ini bertuuan untuk mengetahui keefektifan Hiponimi dalam Pengajaran Kosa Kata. Metode yang digunakan adalah Perbandingan Intact-Group yang merupakan salah satu dari jenis metode Pre-Experimental dimana terdapat grup eksperimen dan grup kontrol. Alat pengumpulan data yang digunakan adalah tes tertulis yang berupa 30 soal pilihan ganda. Berdasarkan data yang diperoleh, secara signifikan Hiponimi dapat meningkatkan pencapaian kosa kata siswa. Hal ini terbukti dari perbedaan nilai rata-rata grup eksperimen (76.96) dan grup kontrol(48.62). Begitu pula nilai besarnya efek dari penggunaan Hiponimi yaitu 1.83 (> 1.00) atau masuk dalam kategori memiliki efek yang kuat. Dengan demikian, dapat disimpulkan bahwa Penggunaan Hiponimi dapat menjadi teknik yang efektif dalam Pengajaran Kosa Kata untuk siswa kelas delapan di MTs Aswaja Pontianak pada tahun ajaran 2014/2015. Kata Kunci : Pengajaran Kosa Kata, Hiponimi